Taxation of Technical Services Income Under Indonesia-Japan Treaty: Case Study of PT XYZ - Gunadi Gunadi (LPPM-STPI, 2020)
As the abundance of employees is available in this country, this subsidiary operates manufacturing where automotive parts are produced and traded. To enable this manufacturing producing and trading these parts, the nonresident MNC license intangibles, e. Under an agreement, the subsidiary pays initial fees therefor. Thereafter, an application of patent right is launched to the Government for this invention and then licensed to the subsidiary. Under the 1983 Income Tax Act as recently was amended in 2008, initial fees with regard to the new product are taxed as business profits where the services are provided more than 60 days otherwise the income items are taxed under Art 26 ITA. Notwithstanding the ITA, however, the 1982 Indonesian-Japanese Tax Treaty does neither include those initial fees in the definition of the term ‘royalties’ nor technical services which creates a permanent establishment. The Treaty limits the services p. only to the furnishing of consultancy or supervisory services in connection with building construction or installation project. Regarding professional services of an independent character, Art 14 Treaty provides criteria for source taxation the fixed base clause, or the rendering of services for a period aggregating more than 183 days within a calendar year. As the non-resident parent is a manufacturing company and this provision pertains to independent personal services a question arises whether Art 14 of the Treaty is relevant to this case.